Lemierre’s syndrome - Eilbert, Wesley (Springer, 2013)
Lemierre’s syndrome is a condition characterized by thrombophlebitis of the internal jugular vein and bacteremia caused by primarily anaerobic organisms, following a recent oropharyngeal infection. This has been an uncommon illness in the era of antibiotic therapy, though it has been reported with increasing frequency in the past 15 years. Lemierre’s syndrome should be suspected in young healthy patients with prolonged symptoms of pharyngitis followed by symptoms of septicemia or pneumonia, or an atypical lateral neck pain. Diagnosis is often confirmed by identification of thrombophlebitis of the internal jugular vein and growth of anaerobic bacteria on blood culture. Treatment involves prolonged antibiotic therapy occasionally combined with anticoagulation. We review the literature and a case of a child with Lemierre’s syndrome.